Comparative Analysis of CAZymes from Trichoderma longibrachiatum LMBC 172 Cultured with Three Different Carbon Sources: Sugarcane Bagasse, Tamarind Seeds, and Hemicellulose Simulation - Alex Graça Contato; Tiago Cabral Borelli; Ana Karine Furtado de Carvalho; Heitor Buzetti Simões Bento; Marcos Silveira Buckeridge; Janet Rogers; Steven Hartson; Rolf Alexander Prade; Maria de Lourdes Teixeira de Moraes Polizeli (Clean Technologies)
The examination of fungal secretomes has garnered attention for its potential to unveil the repertoire of secreted proteins, notably CAZymes (Carbohydrate-Active enzymes), across various microorganisms. This study presents findings on categorizing the secretome profile of CAZymes by their function and family, derived from the filamentous fungus Trichoderma longibrachiatum LMBC 172. The cultivation was performed through submerged fermentation with three distinct carbon sources: sugarcane bagasse, tamarind seeds, and a control simulating hemicellulose containing 0.5% beechwood xylan plus 0.5% oat spelt xylan. The secretome analysis revealed 206 distinct CAZymes. Each carbon source showed particularities and differences. Of these, 89 proteins were produced simultaneously with all the carbon sources; specifically, 41 proteins using only the hemicellulose simulation, 29 proteins when sugarcane bagasse was used as a carbon source, and only 3 when tamarind seeds were used. However, in this last condition, there was a high intensity of xyloglucanase GH74 production, thus reaffirming the richness of xyloglucan in the constitution of these seeds. When evaluating the proteins found in two conditions, 18 proteins were shown between the simulation of hemicellulose and sugarcane bagasse, 11 proteins between the simulation of hemicellulose and tamarind seeds, and 15 proteins between sugarcane bagasse and tamarind seeds. Among the proteins found, there are representatives of different families such as glycosyl hydrolases (GHs) that cleave cellulose, hemicellulose, pectin, or other components; carbohydrate esterases (CEs); polysaccharide lyases (PLs); carbohydrate-binding modules (CBMs); and auxiliary activity enzymes (AAs). These results demonstrate the importance of analyzing CAZymes secreted by microorganisms under different culture conditions.